The Impact of Financial Literacy and Digital Awareness on Investment Intentions - Karundeng, Meidy Lieke; Siagian, Valentine; Hutabarat, Francis; Pangaribuan, Hisar (Yayasan Ilomata, 2024)
Investment intention is one important thing in life. This study investigates the impact of financial literacy and digital awareness on investment intentions. Questionnaires was given to potential and active small medium micro enterprises owners collected via an online survey. The questionnaires were analyzed using descriptive statistics and hypotheses was tested using multiple linear regression The results reveal a positive and significant correlation (0.018) between the two independent variables and investment intentions. The results highlight the importance of financial and digital education in enhancing individuals' propensity to invest, suggesting that improved literacy in these areas can foster greater investment activity. These insights are particularly valuable for policymakers and practitioners looking to bolster investment participation through educational initiatives, underscoring the need to integrate financial and digital literacy into public learning frameworks.